ENVIRONMENTAL ISSUES OF LAND DEGRADATION AT THE CURRENT STAGE (International journal of artificial intelligence, 2026)
This article examines the environmental issues of land degradation at the current stage as one of the negative factors in the modern world in the context of the socioeconomic development of planet Earth's regions. It also examines the environmental problems of land degradation associated with anthropogenic and natural processes that negatively impact the functioning of land within the ecosystem. Furthermore, the issues focus on land degradation, which is the most serious environmental problem in the modern world. Land degradation causes significant economic damage and has numerous negative impacts on agricultural productivity, reducing the fertility of agricultural lands.